DL-AOD Positioning Algorithm for Enhanced 5G NR Location Services - Sosnin, Sergey; Lomayev, Artyom; Khoryaev, Alexey (International Conference on Indoor Positioning and Indoor Navigation, 2021)
In this paper we propose a Downlink Angle of Departure (DL-AOD) positioning algorithm for UE coordinates estimation using channel measurements. The channel estimation is performed with a multi-element transmit antenna array at the base station (gNB) and a single or multi-element receive antenna array at the user device (UE). The algorithm performs total receive channel power maximization with respect to the multi-dimensional space-time filter coefficients to derive an optimal DL-AOD solution. It is shown that the DL-AOD measurements may suffer from the Non-Line of Sight (NLOS) propagation phenomenon, specifically in indoor environments, that causes an angular bias relative to the true Line of Sight (LOS) direction. To reduce the impact of NLOS links on the resulting positioning accuracy the reliability function is introduced for correct weighting of the DL-AOD measurements in the positioning equations. The performance evaluation of the proposed algorithm is provided for the Industrial Internet of Things (I-IoT) use case.